Noticias Breves. Revista de Química; Vol. 29, Núm. 1 (2015) - Ortega San Martín, Luis (2015)
Chemistry: a career with good job opportunities and competitive salaries. Highlight: Chemist from PUCP are awarded a gold Medal in the International Exhibition of Inventions for their innovative proposal in plastics recycling